2000
DOI: 10.1097/00003246-200007000-00068
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin and cytokine levels: Relationship to organ failure and mortality in pediatric septic shock

Abstract: The admission PCT, like TNF and IL-10, is related to the severity of organ failure and mortality in children with septic shock. A fall in PCT after 24 hrs of treatment may have favorable prognostic significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
2
13

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(105 citation statements)
references
References 18 publications
5
85
2
13
Order By: Relevance
“…In our study blood cultures were positive in the samples taken just before death but final results were available after 1 week of death. Correlation of rise in PCT with mortality is similar to studies published earlier [19,20]. The highlighting feature of our study is increase in PCT levels with neutropenic sepsis in adult patients of cardiac ICU.…”
Section: Discussionsupporting
confidence: 91%
“…In our study blood cultures were positive in the samples taken just before death but final results were available after 1 week of death. Correlation of rise in PCT with mortality is similar to studies published earlier [19,20]. The highlighting feature of our study is increase in PCT levels with neutropenic sepsis in adult patients of cardiac ICU.…”
Section: Discussionsupporting
confidence: 91%
“…4 Serum PCT levels have been shown to correlate well with the degree of organ dysfunction, severity of sepsis syndrome, and the length of ICU stay in sepsis and severe bacterial infection. 5 Although, significantly higher PCT levels were found in non-survivors, the ROC analysis in this study showed that PCT is not a useful tool for prognosis.…”
Section: Procalcitonin Levels Do Not Predict Mortality Following Majocontrasting
confidence: 60%
“…Al realizar la búsqueda de literatura existente el estudio de Gómez-Rivera et al (7) , quienes evaluaron 22 pacientes con sepsis observando que la mortalidad al séptimo día se presentó con mayor frecuencia en los pacientes que presentaron procalcitonina > 10ng/mL. Hatherill et al (25) , observaron en 75 niños con sepsis niveles de procalcitonina de 82 ng/mL (supervivientes) vs. 273 ng/mL (no supervivientes) (IC 95%: (0,59 -0,880); aquí se estudió la relación de niveles de procalcitonina, interleuquina 10 y el factor de necrosis tumoral con la mortalidad, concluyendo que niveles elevados de estos tres marcadores séricos se asocian con la mortalidad en niños con choque séptico. Casado-Flores et al (26) , en un estudio de 80 niños con sepsis, reportaron que el valor de la mediana de procalcitonina al ingreso, fue significativamente más alto en los no sobrevivientes, encontrando diferencia estadística significativa en los sobrevivientes (49,6 vs. 16,4 ng/mL) (p = 0,008), consecuente con los hallazgos del presente trabajo (33 vs 6 ng/mL) (IC: 95%: 2,95-38) respectivamente.…”
Section: Discussionunclassified